The Improvement 0f Conservative Characteristic Through Science For Beginner Based On Scientific Approach On Children From 5-6 Years Of Age In TK IT As-Shiddiqy Jepara - Saadah, Tafrikhatus; Tasuah, Neneng (Jurusan PGPAUD FIP UNNES, 2018)
Conservative characteristic aims at boosting care or attention to the surrounding environment. Learning science based on scientific approach is beneficial to find out the reasons and impacts exist in the environment through the process of observation, questionning, collecting and processing information, and communicating. This study aims at finding out the difference of improvement of conservative characteristic through science for beginner based on scientific approach on children from 5-6 years of age. Research method used is quantitative method while research design is experimental design through One Group Pretest-Posttest. The sample used is 30 children on the age of 5-6. Sampling technique used is purposive sample. The result of this research analyzed with Paired Sample t-Test is that the improvement of 38,9 in percentage 38% coming from average value of pretest from 102,27 turning into 141,17 for posttest average score. The increase is started from 25 points up to 57 points. This increase is resulted from t-test with -tcount= -27,422 less than -ttable= -2,045 that is -2,045>-27,422 or 27,422>2,045 with significance value (2-tailed) by 0,00 < 0,05. This means that there is such significant difference on conservative characteristic through science for beginner based on scientific approach on children from 5-6 years of age in TK IT As-Shiddiqy Jepara. Key words: Conservative characteristic, scince for beginner, scientific approach